0509 Effect of CPAP Use on Readmission Rates in Hospitalized Patients With Cardiovascular Disease and SDB. (12th April 2019) - Schwab, Richard; Geng, Eric; Enriquez, Marjon; Blase, Amy; Willes, Leslee; Le, Diana; Benjafield, Adam
Abstract: Introduction: Sleep disordered breathing (SDB) is associated with cardiac-related morbidity and mortality. Hospitalized patients with heart disease are frequently readmitted. We hypothesized that hospitalized patients with cardiovascular disease and newly diagnosed SDB who used CPAP as an outpatient would show reduced cardiac-related readmissions and ER visit rates compared to patients who did not use CPAP. Methods: 127 SDB patients with cardiovascular disease (52 using CPAP, 75 not using CPAP) were followed prospectively in a registry for up to 36 months. CPAP adherence, readmissions/ER visits, mortality, demographic data, LVEF%, pulse oximetry, Epworth Sleepiness Scale (ESS) data were collected. Baseline characteristics were utilized to generate propensity scores, the probability of choosing CPAP treatment, used as weights in statistical comparisons to reduce bias in this non-randomized study. Results: The patients choosing CPAP were more likely to be male, had higher BMI and were twice as likely to have LVEF≥40%. 0% (0/52) of CPAP patients had a cardiac readmission or ER visit in the first 90 days. In the untreated group, 4.1% (3/74) had a cardiac readmission and 2.7% (2/74) had a cardiac-related ER visit. Over one year, 3.8% (2/52) of CPAP patients were readmitted compared to 10.8% (8/74) in the untreated group. 1.9% (1/52) and 4.1% (3/74) of CPAP and non-CPAP patients respectively had an ER visit. In adjusted survival analysis, 0.0% of CPAP patients and 13.3% of non-CPAP patients had a cardiac readmission or death in the first 90 days; 12.3% of CPAP patients and 25.9% of non-CPAP patients had a readmission or death by one year (p=0.3408). In unadjusted survival analysis, 12.0% of CPAP patients compared to 29.6% of non-CPAP patients had a cardiac readmission or death in the first year (p=0.0576). Conclusion: In this study, SDB patients with CPAP trended towards a lower rate of cardiac-related readmission and ER visits, and/or death than those without CPAP. These data suggest that CPAP may assist in lowering cardiac-related readmissions in patients with SDB and cardiovascular morbidity. Support (If Any): Partial funding by ResMed